PENDAMPINGAN PENCIPTAAN BONEKA WAYANG BAGI SISWA DISABILITAS TULI DI PADEPOKAN SENI SAROTAMA KARANGANYAR - Dwiyasmono, Dwiyasmono; Murtono, Taufik; Sri Kuncoro, Jonet (Abdi Seni, 2025)
Persons with disabilities, especially those with hearing impairments, often face significant challenges in accessing and enjoying traditional wayang kulit performances. This community service program seeks to address this issue by introducing innovations in the form of specially designed wayang puppets and the integration of speech balloons (balon kata) to make performances more accessible and engaging for deaf audiences. The aim of this initiative is to empower individuals with hearing disabilities through puppetry arts by creating visually intuitive puppets and providing visual dialogue aids that support their understanding of the narrative and character interactions. The method employed involves a structured design facilitation process that includes problem identification, idea formulation, experimentation, selection, implementation, and presentation. The involvement of community partners such as Padepokan Seni Sarotama is a key component of the program's success. The results show that the use of speech balloons in conjunction with puppet design has significantly improved the level of appreciation, comprehension, and engagement of deaf participants during wayang performances. Participants expressed a stronger emotional connection to the performance and reported increased confidence and self-esteem. This program demonstrates that artistic innovation in traditional puppetry can serve as an effective medium for inclusion and empowerment of individuals with special needs. Additionally, the project contributes to the preservation and revitalization of wayang culture among younger generations, including those with disabilities.